Extracellular matrix content and WNT/β-catenin levels of cartilage determine the chondrocyte response to compressive load - Praxenthaler, Heiko; Krämer, Elisabeth; Weisser, Melanie Bianca; Hecht, Nicole; Fischer, Jennifer; Großner, Tobias; Richter, Wiltrud (Biochimica et biophysica acta. Molecular basis of disease, 2018)
During osteoarthritis (OA)-development extracellular matrix (ECM) molecules are lost from cartilage, thus changing gene-expression, matrix synthesis and biomechanical competence of the tissue. Mechanical loading is important for the maintenance of articular cartilage; however, the influence of an altered ECM content on the response of chondrocytes to loading is not well understood, but may provide important insights into underlying mechanisms as well as supplying new therapies for OA. Objective here was to explore whether a changing ECM-content of engineered cartilage affects major signaling pathways and how this alters the chondrocyte response to compressive loading. Activity of canonical WNT-, BMP-, TGF-β- and p38-signaling was determined during maturation of human engineered cartilage and followed after exposure to a single dynamic compression-episode. WNT/β-catenin- and pSmad1/5/9-levels declined with increasing ECM-content of cartilage. While loading significantly suppressed proteoglycan-synthesis and ACAN-expression at low ECM-content this catabolic response then shifted to an anabolic reaction at high ECM-content. A positive correlation was observed between GAG-content and load-induced alteration of proteoglycan-synthesis. Induction of high β-catenin levels by the WNT-agonist CHIR suppressed load-induced SOX9- and GAG-stimulation in mature constructs. In contrast, the WNT-antagonist IWP-2 was capable of attenuating load-induced GAG-suppression in immature constructs. In conclusion, either ECM accumulation-associated or pharmacologically induced silencing of WNT-levels allowed for a more anabolic reaction of chondrocytes to physiological loading. This is consistent with the role of proteoglycans in sequestering WNT-ligands in the ECM, thus reducing WNT-activity and also provides a novel explanation of why low WNT-activity in cartilage protects from OA-development in mechanically overstressed cartilage.